a Beyond Perception Scores: Structural Patterns In Employee Voice, Safety Climate, And Organizational Trust - Efie Indrianti; Juan Prianto; Angelica Kurnia Herjandi; Robinson Manalu; Martiningsih (Sekolah Tinggi Teknologi Wastukancana, 2026)
This study explores how employees perceive organizational trust, safety climate, and their ability to express opinions (employee voice) in a labor-intensive textile manufacturing environment. The analysis is based on survey data from 2,605 employees, which is compared with the organization’s target score (95.14) and previous performance (94.70). A construct-based approach is used, focusing on four main dimensions: Employer Advocacy, Employee Voice, Safety Climate, and Perceived Knowledge Capability. The data are analyzed using descriptive statistics, comparisons across periods, and distribution patterns. The results show that the overall score remains consistently high (M=95.48), exceeding both the target and prior results. This indicates that employees generally have a positive and stable perception of their work environment. Most responses are concentrated in the highest category, with more than 82% of employees choosing “strongly agree.” While this reflects strong alignment, it also suggests that the measurement may need to be more sensitive to capture deeper insights. At the construct level, Employee Voice and Safety Climate show particularly strong performance. However, Perceived Knowledge Capability still offers room for improvement, especially in areas such as occupational health awareness, understanding of procedures, and knowledge of labor rights. Improvements are seen across all dimensions, indicating a positive overall trend. This study highlights the importance of combining perception-based surveys with behavioral data and competency validation. Such an approach can support continuous improvement, strengthen employee capabilities, and improve decision-making